2019
DOI: 10.2196/12515
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Training in Undergraduate Medical Education: Mixed-Methods Review

Abstract: Background Telemedicine has grown exponentially in the United States over the past few decades, and contemporary trends in the health care environment are serving to fuel this growth into the future. Therefore, medical schools are learning to incorporate telemedicine competencies into the undergraduate medical education of future physicians so that they can more effectively leverage telemedicine technologies for improving the quality of care, increasing patient access, and reducing health care exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
215
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(224 citation statements)
references
References 16 publications
1
215
0
8
Order By: Relevance
“…Healthcare provision through telemedicine will become the mainstream in the coming years. Indeed, studies have found that interaction with telemedicine technologies during undergraduate medical training contributes to improved core competencies, medical knowledge, overall learning and higher quality patient care [3].…”
Section: Teleteaching and Telemedicinementioning
confidence: 99%
“…Healthcare provision through telemedicine will become the mainstream in the coming years. Indeed, studies have found that interaction with telemedicine technologies during undergraduate medical training contributes to improved core competencies, medical knowledge, overall learning and higher quality patient care [3].…”
Section: Teleteaching and Telemedicinementioning
confidence: 99%
“…Students voiced positive experiences participating in telehealth encounters through pre-clinical electives and volunteer efforts, allowing them to practice essential skills like taking histories, presenting to attending physicians, and writing notes. Studies found that interaction with telehealth during medical school contributes to improved core competencies, medical knowledge, overall learning and higher quality patient care (9). The increased reliance on telemedicine should motivate allocation of structured time in the pre-clinical curriculum for telehealth training, which may include electronic health record (EHR) training as well, to equip students with the practical skills they will need to succeed in an evolving clinical landscape.…”
Section: Clinical Skills Learning: Shortfalls and Opportunities For Gmentioning
confidence: 99%
“…Moreover, formal training in conducting virtual visits is limited, even among those who may have some experience with telemedicine, 10 as few medical schools offer telemedicine education. 11 Given the unprecedented need for connecting with patients virtually during the COVID-19 era, it is important to consider how clinicians can translate their experience with in-person visits to virtual visits. These skills are increasingly important as telemedicine becomes an integrated part of our routine care delivery system, both as a primary modality for outpatient visits and for triaging patients who may require in-person evaluation.…”
Section: Introduction: Telemedicine Without the Trainingmentioning
confidence: 99%